Famílias : um estudo sociojurídico acerca das subjetividades e das regulações do Estado - Silva, Camila Raquel Palmeira da (2022)
This study analyzed contemporary family arrangements and the legitimacy of families that are constituted differently from marriage. The family stands out as the holder of special protection from the State through its regulation and the need to observe the autonomy of the will of the parties. The common law marriage, a family institute without mandatory contractual bond, has undergone several changes, which for the most part, bring this institute closer to marriage. In order to investigate the guarantees and exercise of autonomy in establishing a family, a qualitative research was developed, with semi-structured interviews with members of families that are different from the hegemonic pattern. In order to analyze the data obtained through the research, a historical contextualization of the family institutes and the changes in social behavior that impacted the concept of family was necessary, both in terms of conjugality and parenting. Autonomy, self-determination, function within the family group, the strengthening of affection within the family nucleus were some aspects of greater emphasis in the data analysis.